2021
DOI: 10.1002/adma.202103953
|View full text |Cite
|
Sign up to set email alerts
|

Au‐Doped Ag2Te Quantum Dots with Bright NIR‐IIb Fluorescence for In Situ Monitoring of Angiogenesis and Arteriogenesis in a Hindlimb Ischemic Model

Abstract: Fluorescence located in 1500–1700 nm (denoted as the near‐infrared IIb window, NIR‐IIb) has drawn great interest for bioimaging, owing to its ultrahigh tissue penetration depth and spatiotemporal resolution. Therefore, NIR‐IIb fluorescent probes with high photoluminescence quantum yield (PLQY) and stability along with high biocompatibility are urgently pursued. Herein, a novel NIR‐IIb fluorescent probe of Au‐doped Ag2Te (Au:Ag2Te) quantum dots (QDs) is developed via a facile cation exchange method. The Au dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 42 publications
0
59
0
Order By: Relevance
“…In addition, the improvement of PLQY was accompanied by the increase of lifetime (Tables S3–S5), which was also reported in the research on Au-doped Ag 2 Te QDs . As mentioned above, the precise regulation of the Ag precursor reactivity is conducive to the improvement of the crystallinity of QDs and surface reconstruction. Thus, the nonradiative transition may be suppressed, resulting in the increase of PLQY and lifetime. , Overall, the higher PLQY of QDs synthesized in the TPP-containing system was attributed to the accurately regulated the Ag precursor reactivity by TPP.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, the improvement of PLQY was accompanied by the increase of lifetime (Tables S3–S5), which was also reported in the research on Au-doped Ag 2 Te QDs . As mentioned above, the precise regulation of the Ag precursor reactivity is conducive to the improvement of the crystallinity of QDs and surface reconstruction. Thus, the nonradiative transition may be suppressed, resulting in the increase of PLQY and lifetime. , Overall, the higher PLQY of QDs synthesized in the TPP-containing system was attributed to the accurately regulated the Ag precursor reactivity by TPP.…”
Section: Resultsmentioning
confidence: 89%
“…In addition, the improvement of PLQY was accompanied by the increase of lifetime (Tables S3−S5), which was also reported in the research on Au-doped Ag 2 Te QDs. 57 As mentioned above, the precise regulation of the Ag precursor reactivity is conducive to the improvement of the crystallinity of QDs and surface reconstruction. Thus, the nonradiative transition may be suppressed, resulting in the increase of PLQY and lifetime.…”
Section: Resultsmentioning
confidence: 97%
“…Dodecanethiol-capped Ag 2 Te QDs (DT-QDs) were synthesized by a hot-injection method according to the reported literature. , The X-ray photoelectron spectra (XPS) results showed that the prepared products consisted of Ag and Te elements. In addition, XPS peaks at 367.2 and 373.2 eV corresponded to the Ag 3d orbital, and peaks at 581.8 and 571.4 eV were ascribed to the binding energy of the Te 3d orbital (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Quantum dots (QDs) with near-infrared (NIR) excitation and NIR-IIb (1500–1700 nm) emission have shown great prospect in luminescence imaging due to the depressed photon absorption and scattering by biological samples, large tissue penetration depth, and high imaging contrast and resolution. Compared with previously reported NIR-IIb emissive QDs, such as InAs QDs, PbS QDs, HgTe QDs, etc., Ag 2 Te QDs without any highly toxic elements have recently attracted wide attention due to their decent biocompatibility. However, the poor luminescence brightness of Ag 2 Te QDs prevents their practical applications. For this matter, shell coating and Au doping methods were reported to enhance the luminescence via improving the photoluminescence quantum yield. , Meanwhile, these methods not only need to meet the challenge of lattice mismatch but also increase the difficulty of synthesis. Therefore, it is of great significance to explore more strategies for elevating the luminescence efficiency of Ag 2 Te QDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation